Development and Validation of Mathematical Critical Thinking Ability Instrument Using Rasch Measurement - Nur Afifah; Tasya Pebrianti; Ayu Faradillah; Syafika Ulfah (Universitas Teknokrat Indonesia, 2026)
This instrument has been confirmed to be suitable for measuring students' mathematical thinking skills. It’s validity and reliability have been confirmed through verification, including Wright Map analysis conducted using Winstep software. This research is important to produce a valid, reliable, and Wright map instrument for mathematical critical thinking skills. A properly developed instrument will help measure students' abilities more accurately and objectively. This research utilized a quantitative methodology through the application of a survey approach, The data was obtained by applying a tool for measuring critical thinking skills in mathematics to 299 10th grade students at a secondary school in North Jakarta. This measurement instrument consists of three questions covering four indicators of critical thinking skills in mathematics. The measurement tool consists of three questions with four indicators of mathematical critical thinking skills. The validity test results show that all three questions are valid based on the three categories in the item fit order table. Additionally, in the reliability test using Cronbach's Alpha (KR-20), the results showed that the questions were reliable with a value of 0.75. The results of the Wright Map analysis showed two categories, namely indicators and gender. In the indicator category, students have difficulty in drawing conclusions from the results obtained, which are included in the inference indicator. Meanwhile, the gender category shows that female students have higher mathematical critical thinking skills than male students with a percentage value of 16.38%. Proven instruments can help teachers to accurately support and assess the development of students' cognitive abilities.Keywords: validity, reliability, Wright map, Rasch, mathematical critical thinking skills.